The Impact of Google Classroom in Character Education Based on Tabe Culture in the Era of Industrial Revolution 4.0 - Sagir M Amin; Moh Ali (International Journal of Education and Humanities, 2022)
Along with the rapid development of communication and information technology in the industrial revolution 4.0. in which online-based learning (for example, google classroom and many more learning providers) is inevitable, has currently had strong implications for the world of education and learning. In higher education, google classroom as an online provider has been found very helpful and made it easier for educators and students to do activities in the online learning and teaching process. This is an advantage of current technology and information development. However, the use of google classroom predominantly helps students develop their cognitive domain but fails to help them build their character building. In fact, inculcating tabe-based characters one of the cross generations type of established culture in the Buginese Tribe in the industrial revolution 4.0 era has a deep meaning in our society. These include sense of respect each other, saying good and polite words as well as writing them politely, having good attitudes and behaviour and not writing sentences that potentially disturbs or offend one another. These types of behaviour and attitudes are those contained in the cultures of Buginese tribe as Sipakatau (respect each other), Sipakalebbi (be humanized to each other) and Sipakainge (to remind of bad deeds to each other). The results show that the use of the google classroom online learning provider has a very positive impact on increasing Intelligence Quotient of students but has failed to inculcategood character to them as they use slang in their conversations like up, yoi, ok, siap, gtw, cancer, gan, mastah, hqq and kuy. goblok, edan, santuy, sob, kepo, woles, baper, nooband regand tend to be rude